Analysis Of Consumer Satisfaction On Service Quality At Asian Motor Workshops In South Lampung - Serlin, Serlin; Alam, Iskandar Ali (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
Asian Motor Workshop is a company engaged in motorcycle repair services. The research aims to analyze and determine the satisfaction of workshop visitors. This type of research is quantitative with a population of 215 and a sample of 100 visitors. This study used a questionnaire as a data collection technique, which contained 15 statements, using the methodNonprobability sampling. Analysis tool usingImportance Performance Anaysis (IPA), with four dimensions to measure which include; Physical Appearance, Reliability, Responsiveness, Reliability, Assurance, and Empathy. Analysis results states in quadrant A Physical facilities, namely items 25 and 23. Quadrant B must be maintained, namely items 2, 3, 4, and 5, Responsiveness, namely items 7, 8, and 10, Assurance, namely items 11, 13, and 14, and Empathy, namely item number 18. Quadrant C which is considered less important is item number 1, items 6, 9, 16, 17, 21 and 24.